Short and long‐term outcomes of three‐dimensional printed surgical guides and virtual surgical planning versus conventional methods for fibula free flap reconstruction of the mandible: Decreased nonunion and complication rates. Issue 8 (31st March 2021) - May, Matthew M.; Howe, Benjamin M.; O'Byrne, Thomas J.; Alexander, Amy E.; Morris, Jonathon M.; Moore, Eric J.; Kasperbauer, Jan L.; Janus, Jeffrey R.; Van Abel, Kathryn M.; Dickens, Hunter J.; Price, Daniel L.
Abstract: Background: To determine whether virtual surgical planning and three‐dimensional printed cutting guides (3D/VSP) improved radiographic bone union compared to conventional methods (CM) in fibula free flap (FFF) reconstruction of the mandibles. Methods: Retrospective study from the years 2000–2018 at a tertiary hospital. Osseous union was evaluated by a radiologist blinded to each patient's treatment. Results: Two hundred sixty patients who underwent FFF tissue transfer, 28 with VSP and 3D cutting guides. Bony union was not achieved in 46 (20%) patients who underwent CM compared to 1 (4%) of patients with VSP and guides ( p = 0.036). FFF complication was significantly higher in CM with 87 patients (38%) compared to three patients (11%) in 3D/VSP ( p = 0.005). Median time to bony union for patients who underwent CM was 1.4 years compared to 0.8 years in 3D/VSP. Conclusions: 3D/VSP reduced the rate of radiographic nonunion and flap‐related complications in FFF reconstruction for mandibular defects.